British rule of law under terrorist attack: The right to liberty and derogation from the European Convention on Human Rights in the United Kingdom - Valtonen, Terhi (My University, 2003)
Everyone’s right to liberty is protected in the European Convention on Human Rights and also in most states’ constitutions. All the contracting parties to the Convention are committed to protect the Convention’s rights and freedoms, and they must also accept the principles of the rule of law. Since the United Kingdom has lacked a written constitution, the rule of law has played an important role as a principle of institutional morality. The Human Rights Act brought the fundamental rights set out in the Convention into the domestic law of the United Kingdom. All the public bodies have to take the Convention rights into consideration in their actions and the courts have to review the compatibility of parliamentary legislation with the Convention rights to ensure not to offend those rights. The terrorist attacks to the US on 11 September 2001 lead to western states’ strict legislative measures to fight against terrorism. The United Kingdom’s legislative response to those attacks was the enactment of the Anti-Terrorism, Crime and Security Act, which enables indefinite detention of suspected international terrorists without trial. The United Kingdom had to enter a formal derogation from the Convention to be able to carry the provisions of detention in this Act into effect. The study seeks to examine how proportionate the detention measures under the United Kingdom’s Anti-Terrorism, Crime and Security Act are in relation to the “war against terrorism” and whether they are justifiable in a free and democratic society, which institutional morality is based on the rule of law. It is important to examine where can a line be drawn in legislating against terrorism when democracy and fundamental rights have to be protected at the same time. The study concentrates on valid law in the United Kingdom and has comparative features when it is compared to other European countries. This is important because although the United Kingdom was the only contracting party to the Convention, which deemed it necessary to derogate from the Convention’s obligations after the 11 September, the same threat of terrorism can be directed to several other European countries. To be able to understand why the provisions of the Anti-Terrorism, Crime and Security Act are so controversial, a case that was concerned with the legality of these provisions, is examined as an example. It became evident that the detention of suspected international terrorists was discriminatory against them by reason of their nationality. The detention measures were defended by the fact that it was a matter of immigration, and thus they were not discriminatory. Therefore it seems that the United Kingdom has a two-track legal system, in which there are different human rights standards applied to foreigners and nationals. The final result is that the rule of law cannot prohibit states from enacting discriminatory laws, but still it is supposed to protect the individuals from discriminatory enforcement of the law.
Keywords: Human rights; United Kingdom; rule of law; emergency legislation; derogation of rights; fi=Julkisoikeus : hallinnon juridiikan vertaileva ohjelma|